OS X for hackers at heart - Potter, Bruce (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2005)
OS X 10.4 Tiger is a major upgrade for Mac OS X for running Apples Macintosh computers and laptops. This book teaches hackers of all types from software developers to security professionals to hobbyists, how to use its features for wireless networking, WarDriving, software development, penetration testing, scripting administrative tasks, and more.
Cover -- Contents -- Foreword -- Chapter 1 A Network Admin's Guide to Using Mac OS X -- Running a Headless Mac -- Adding Interfaces to the Mac -- The Macintosh as a Router -- Mac OS X as a RADIUS server -- Summary -- Solutions Fast Track -- Frequently Asked Questions -- Chapter 2 Automation -- Using Automator -- Understanding AppleScript -- Bash Scripting -- Using Bash, AppleScript, and Automator Together! -- Summary -- Solutions Fast Track -- Links to Sites -- Frequently Asked Questions -- Chapter 3 OS X in a Microsoft Environment -- Accessing Network File Systems -- NTLM Authentication -- Connecting to a Windows PPTP Server -- Zen of Running Windows Boxes from a Mac -- Summary -- Solutions Fast Track -- Frequently Asked Questions -- Chapter 4 WarDriving and Wireless Penetration Testing with OS X -- WarDriving with KisMAC -- Penetration Testing with OS X -- Other OS X Tools for WarDriving and WLAN Testing -- Summary -- Solutions Fast Track -- Frequently Asked Questions -- Chapter 5 Mac OS X for Pen Testers -- The OS X Command Shell -- Compiling and Porting Open Source Software -- Using The "Top 75 Security Tools" List -- Installing and Using The "Big" Tools -- Other OS X "Must Haves" -- Summary -- Solutions Fast Track -- Frequently Asked Questions -- Chapter 6 Mac Tricks (Stupid Powerbook Stunts That Make You Look Like a God) -- Desktop Console -- Screen Savers -- Widgets -- Apple Motion Sensor -- VNC with Apple Remote Desktop -- Gestures -- Sogudi -- GUI Scripts -- Summary -- Solutions Fast Track -- Frequently Asked Questions -- Chapter 7 OS X For the Road Warrior -- Safe and Secure E-mail -- Battery Management -- Summary -- Solutions Fast Track -- Frequently Asked Questions -- Appendix A Hacking the iPod -- Opening Your iPod -- Replacing the iPod Battery -- Upgrading a 5GB iPod's Hard Drive -- From Mac to Windows and Back Again -- iPod Diagnostic Mode -- Additional iPod Hacks -- iPod Resources on the Web -- Index -- Last Page.
Keywords: Mac OS; Operating systems (Computers).; Electronic books